Synthesis of Ziegler-Natta Catalyst using Malaysian Ilmenite Derived TiCl4 via Recrystallization Method: A Statistical Approach - Sanjith Udayakumar; Najwa Ibrahim; Chan Yong Chien; Shaikh Abdul Rahman Shaik Abdul Wahab; Ahmad Fauzi Mohd Noor; Sivakumar Ramakrishnan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
In the current study, Ziegler-Natta (Z-N) catalyst was synthesized via recrystallization method using MgCl2 as a support, AlCl3 as an activator and TiCl4 as a transition metal source. The TiCl4 used in the study was derived from Malaysian ilmenite through a sequential pyrometallurgical and hydrometallurgical process of ilmenite concentrate conversion to TiCl4. The recrystallization method of synthesis of the heterogeneous Z-N catalyst was studied by varying the synthesis parameters, such as the combined amount of MgCl2 and AlCl3, temperature, and amount of TiCl4, using statistical design of experiments. The investigation aimed at determining the best conditions for synthesizing the heterogeneous Z-N catalyst. The synthesis conditions posed a significant influence on the Ti content present in the catalyst product. The morphological and elemental analysis of SEM-EDX showed good spherical nature of the prepared catalysts. The XRD phase analysis detected the peaks of MgCl2, MgCl2-Ethanol, MgCl2/TiClx, and TiO2. The IR spectra confirmed the presence of the Mg-Cl bond at 1635 cm−1 and Ti-Cl bonds at 602 cm-1 and 498 cm-1. The produced catalyst contained a small amount of TiO2, which could be due to the seepage of moisture during the analysis or storage of the sample. The most favourable combination of the studied parameters was determined based on the Ti content in the catalyst product. Therefore, the best conditions for synthesizing the heterogeneous Z-N catalyst with high Ti content (181.1 mg/L) was at a combined amount of 2 g of MgCl2 for 6 g of AlCl3, crystallization temperature of 80 °C, and 2 mL dosage of TiCl4. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).